Effect of post-harvest ripening and drying methods on seed quality and storability in pumpkin cv Pusa Hybrid 1 - KUMAR, VINOD; TOMAR, B S; SINGH, BALRAJ; KUMAR, SANJAY (The Indian Journal of Agricultural Sciences, 2014)
An investigation was carried out, to study the effect of post-harvest ripening and drying methods on the seed quality in pumpkin cv Pusa Hybrid 1, during summer 2008 and 2009 at Seed Production Unit, IARI, New Delhi. After harvesting, the fruits were allowed for post-harvest ripening (PHR) of zero days (P0), 10 days (P1) and 20 days (P2) and seeds obtained from each of the PHR treatments were subjected to three methods of drying, viz. shade drying (D1), sun drying (D2) and mechanical drying (D3). The results showed that seed obtained from 20 days PHR followed by shade drying (P2D1) had given superior quality seed with respect to germination (94.33 %), seedling length (34.30 cm), vigour index - I (3236.52) and electrical conductivity (17.30 m mhos/cm/g) followed by P2D3 (20 days PHR and mechanical drying), while germination (%) was significantly lower in PoD2 during storage. In all treatments the seeds stored for 12 months showed maximum germination followed by reduction after eighteen months of storage. The germination percentage was maintained above the Indian minimum seed certification standards (IMSCS) of 60% up to eighteen months of storage in all treatments.